A high temperature resistant foamed silica gel material and preparation method thereof

By introducing vinyl polyborosilane and inorganic nanofillers into foamed silicone materials, combined with supercritical CO2 foaming and post-sulfurization processes, the problem of poor flame retardant performance of foamed silicone materials is solved, and its thermal stability and flame retardant performance are significantly improved.

CN119219964BActive Publication Date: 2025-04-08ANHUI SMART NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411576366.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-04-08
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The flame retardant properties of foamed silicone materials are poor, they are easy to decompose and burn in open flames, release a large amount of heat and smoke, and the carbon layer formed after combustion is weak, which limits its application.

Method used

By introducing vinyl polyborosilane and inorganic nanofillers into the foamed silicone material, a composite material is formed, and supercritical CO2 foaming and post-sulfurization processes are adopted to improve the thermal stability and flame retardant properties of the material.

Benefits of technology

It significantly improves the thermal stability and flame retardant properties of foamed silicone materials, reduces the heat release rate during combustion, enhances the strength of the carbon layer, and extends the application range of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high temperature resistant foamed silica gel material and a preparation method thereof, belonging to the technical field of silicone rubber, and the preparation method comprises the following steps: the first step, according to parts by weight, 95-97 parts of methyl vinyl silicone rubber and 3-5 parts of vinyl polyborosilane are added to an internal mixer for plasticizing, then 4 parts of hydroxy silicone oil and 40 parts of white carbon black are added for mixing, and a rubber compound is obtained by cooling, and then 2-3 parts of inorganic nanofillers and 2 parts of vulcanizing agents are added to the rubber compound for thinly passing through at room temperature to obtain a composite material; the second step is to pre-vulcanize the composite material; then supercritical CO2 foaming is performed, and finally post-vulcanization is performed. In the present invention, the flame retardant properties of the foamed silica gel material are improved by regulating the amount of inorganic nanofillers and vinyl polyborosilane. Among them, the introduction of vinyl polyborosilane can not only broaden the damping temperature range to realize the regulation of thermodynamic properties in a large range, but also participate in subsequent cross-linking, and has better stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silicone rubber, and in particular relates to a high temperature resistant foamed silicone material and a preparation method thereof. Background Art

[0002] Foamed silicone is often called sponge silicone rubber or microporous silicone rubber. Foamed silicone material is a porous polymer elastomer formed by silicone rubber after foaming. It has the excellent high and low temperature resistance, weather resistance, and radiation aging resistance of silicone rubber and the characteristics of low relative density, high specific surface area, and large compressible deformation of foam materials. It is an excellent material for damping, sound insulation, cushioning, and shock absorption.

[0003] While foamed silicone materials have high thermal stability, they also have certain flammability and are prone to decomposition and combustion when exposed to open flames. Foamed silicone materials have a large number of micropores, which provide opportunities for airflow to enter during combustion. During the combustion process, a pore structure will be generated inside, causing the combustion to intensify and release a large amount of heat and smoke, posing a huge threat to the human body and the environment. In addition, the charcoal layer formed after combustion is relatively weak, which limits the application of foamed silicone materials.

[0004] Adding inorganic flame retardants is an effective way to improve the flame retardant properties of foam silicone rubber. Commonly used inorganic flame retardants include magnesium hydroxide (MH), calcium carbonate (CC), aluminum hydroxide (ATH), etc. For example, the patent application with publication number CN106189260A discloses a silicone foam material and a preparation method thereof, in which the flame retardant properties of the silicone foam material are improved by adding inorganic flame retardants. These flame retardants can release non-combustible gases at high temperatures to form a protective layer, thereby inhibiting combustion. However, the amount and dispersibility of the flame retardant have a negative impact on the mechanical properties of the material, especially a high content of flame retardant will lead to a decrease in the mechanical properties of the material. Summary of the invention

[0005] The object of the present invention is to provide a high temperature resistant foamed silicone material and a preparation method thereof, so as to solve the problem that the foamed silicone material has poor flame retardancy.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a high temperature resistant foamed silica gel material comprises the following steps:

[0008] The first step is to add 95-97 parts of methyl vinyl silicone rubber and 3-5 parts of vinyl polyborosilane into an internal mixer for plasticization, then add 4 parts of hydroxy silicone oil and 40 parts of white carbon black for mixing, and cool to obtain a rubber mixture, and add 2-3 parts of inorganic nanofiller and 2 parts of vulcanizing agent to the rubber mixture and thinly pass at room temperature to obtain a composite material;

[0009] The second step is to pre-vulcanize the composite material; then perform supercritical CO2 foaming, and finally perform post-vulcanization to obtain a high temperature resistant foamed silicone material.

[0010] Furthermore, in the first step, the plasticizing conditions are: temperature of 100-105° C. and rotation speed of 55-60 r / min.

[0011] Furthermore, the pre-curing conditions in the second step are: pre-curing at 125°C and 10MPa for 4-8min;

[0012] The conditions for supercritical CO2 foaming are: foaming temperature 60°C, foaming pressure 6MPa;

[0013] The post-vulcanization conditions are as follows: the foamed sample is vulcanized at 165°C and a pressure of 100 bar for 40 min, and then heat treated at 190°C for 3 h.

[0014] Furthermore, the inorganic nanofiller is one of carbon nanotubes, nano-montmorillonite, and layered graphite oxide.

[0015] Furthermore, the vinyl polyborosilane is obtained by a polycondensation reaction of phenylboric acid and an unsaturated silane coupling agent.

[0016] Furthermore, the molar ratio of the phenylboric acid to the unsaturated silane coupling agent is 1.5-2:1.

[0017] Furthermore, the unsaturated silane coupling agent is at least one of 3-trimethoxysilane propyl acrylate, γ-methacryloxypropyl trimethoxysilane, vinyl trimethoxysilane and allyl trimethoxysilane.

[0018] Furthermore, the molar fraction of vinyl in the methyl vinyl silicone rubber is: 0.13% to 0.20%;

[0019] The specific surface area of ​​white carbon is 200±30m 2 / g;

[0020] The inherent viscosity of hydroxyl is 100CS.

[0021] Furthermore, the vinyl polyborosilane is prepared by the following steps:

[0022] Under nitrogen protection, phenylboric acid and 1,2-dichloroethane were mixed, heated to dissolve, and then an unsaturated silane coupling agent was added. The mixture was stirred at 80°C for 8 hours, then cooled to 20°C, allowed to stand for 8 hours, concentrated under reduced pressure to remove the solvent, and dried under vacuum at 60°C to constant weight to obtain vinyl polyborosilane.

[0023] A high temperature resistant foamed silica gel material is prepared by the above preparation method.

[0024] Beneficial effects of the present invention:

[0025] The main chain of the foamed silica gel material in the present invention is an inorganic SiO bond. In the present invention, vinyl polyborosilane is used as a raw material to introduce a BO segment into the main chain of the foamed silica gel material. After the boron atom enters the main chain of the molecule, the bond energy of the introduced BO is 537.6KJ / mol, which is higher than the bond energy of SiO. In addition, the boron element has a stabilizing and free effect. Therefore, the addition of vinyl polyborosilane can improve the thermal stability and thermal oxygen stability of the foamed silica gel material. At the same time, the introduction of the boron-containing raw material can be converted into SiO2 and B2O3 during the heat treatment process; not only can the heat resistance of the foamed silica gel material be improved, but also the addition of vinyl polyborosilane in the raw material has a promoting effect on the flame retardant effect of the foamed silica gel material, and can synergistically improve the flame retardant performance with the nano filler.

[0026] Nano-scale materials have a series of effects produced by a very large specific surface area, and have the advantages of low density, high mechanical strength, low air absorption and air permeability. In the present invention, by adding inorganic nano-fillers, the carbonization of polymers is promoted, the heat release rate during the combustion of polymers is reduced, and the flame retardant properties are improved. The amount used is small, and adding 0.1%-5% can achieve a good synergistic effect (a small amount of addition has a small effect on mechanical properties). In the present invention, the amount of inorganic nano-fillers added is 2%-3% (relative to the total amount of methyl vinyl silicone rubber and vinyl polyborosilane). The added inorganic nano-fillers can penetrate into the polymer matrix to form a network, which has the effect of improving the flame retardancy of the polymer.

[0027] In the present invention, vinyl polyborosilane is used as a raw material, and not only BO is introduced into the structure of the high-temperature resistant foamed silica gel material (having a dynamic bond effect to limit the movement of chain segments, effectively reducing the sensitivity to temperature, increasing the internal friction of the chain segment movement, and improving the damping performance) but also a phenyl group is introduced (π-π interaction, increasing the intramolecular friction and improving the loss factor). The introduction of vinyl polyborosilane can not only broaden the damping temperature range to achieve the regulation of thermodynamic properties in a larger range, but also participate in subsequent cross-linking and have better stability.

[0028] In the present invention, the flame retardant properties of the foamed silicone material are improved by regulating the dosage of inorganic nanofillers and vinyl polyborosilane. However, the addition of too much inorganic nanofillers and vinyl polyborosilane will cause the high-temperature resistant foamed silicone material matrix to accumulate and form agglomerates. The agglomerates will form nucleation points during the foaming process, and then form large-aperture bubbles, which will affect the improvement of damping performance. Therefore, in the present invention, the performance of the foamed silicone material is improved by regulating the dosage of inorganic nanofillers and vinyl polyborosilane. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The molar fraction of vinyl in the methyl vinyl silicone rubber added in the embodiment of the present invention is 0.13% to 0.20%; the specific surface area of ​​white carbon black is 200±30m 2 / g; the inherent viscosity of hydroxyl group is 100CS.

[0031] Preparation Example 1

[0032] Preparation of vinyl polyborosilane:

[0033] Under nitrogen protection, phenylboric acid and 1,2-dichloroethane were mixed, heated to dissolve, and then γ-methacryloxypropyltrimethoxysilane was added, stirred at 80°C for 8 hours, then cooled to 20°C, allowed to stand for 8 hours, concentrated under reduced pressure to remove the solvent, and dried at 60°C in vacuum to constant weight to obtain vinyl polyborosilane. The molar ratio of phenylboric acid to γ-methacryloxypropyltrimethoxysilane was 1.5:1.

[0034] Preparation Example 2

[0035] Preparation of vinyl polyborosilane:

[0036] The difference between this preparation example and preparation example 1 is that γ-methacryloxypropyltrimethoxysilane is replaced by 3-trimethoxysilane propyl acrylate; the other raw materials and preparation process remain the same as those in preparation example 1.

[0037] Preparation Example 3

[0038] Preparation of vinyl polyborosilane:

[0039] The difference between this preparation example and preparation example 1 is that the molar ratio of γ-methacryloxypropyltrimethoxysilane is 1.8:1; the other raw materials and preparation process remain the same as those in preparation example 1.

[0040] Preparation Example 4

[0041] Preparation of vinyl polyborosilane:

[0042] The difference between this preparation example and preparation example 1 is that the molar ratio of γ-methacryloxypropyltrimethoxysilane is 1.2:1; the other raw materials and preparation process remain the same as those in preparation example 1.

[0043] Example 1

[0044] This embodiment provides a high temperature resistant foamed silica gel material, which is prepared by the following steps:

[0045] The first step is to add 97 parts of methyl vinyl silicone rubber and 3 parts of vinyl polyborosilane prepared in Preparation Example 1 into an internal mixer according to parts by weight, set the temperature range to 100°C and the speed range to 60r / min, and plasticize for 3 minutes, then add 4 parts of hydroxy silicone oil and 40 parts of white carbon black, continue mixing for 25 minutes, cool to obtain a rubber compound, and then add 2 parts of carbon nanotubes (inorganic nanofiller) and 2 parts of vulcanizing agent (diisopropylbenzene peroxide) to the rubber compound, and pass it on a double roller for 30 times at room temperature to obtain a composite material;

[0046] In the second step, the composite material is pre-vulcanized on a flat vulcanizer at 125°C and 10MPa for 5 minutes (the thickness of the film is 4mm); then supercritical CO2 foaming is carried out, and the conditions for supercritical CO2 foaming are a foaming temperature of 60°C and a foaming pressure of 6MPa; finally, a high-temperature resistant foamed silicone material is obtained through post-vulcanization, and the post-vulcanization conditions are: the foamed sample is vulcanized at 165°C and a pressure of 100bar for 40 minutes, and then heat-treated at 190°C for 3 hours to obtain a high-temperature resistant foamed silicone material.

[0047] Embodiment 2 to Embodiment 6, a high temperature resistant foamed silica gel material is different from Embodiment 1 only in that the ratio of the raw materials is adjusted, as shown in Table 1:

[0048] Table 1

[0049] project Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Methyl vinyl silicone rubber 97 97 95 95 96 96 Vinyl polyborosilane 3 3 5 5 4 4 Hydroxy silicone oil 4 4 4 4 4 4 White Carbon Black 40 40 40 40 40 40 Inorganic nanofillers 2 3 2 3 2 3 Vulcanizing agent 2 2 2 2 2 2

[0050] Example 7

[0051] Compared with Example 1, in this example, vinyl polyborosilane is replaced by vinyl polyborosilane prepared in Preparation Example 2, and the remaining raw materials and preparation process remain the same as in Example 1.

[0052] Example 8

[0053] Compared with Example 1, in this example, vinyl polyborosilane is replaced by vinyl polyborosilane prepared in Preparation Example 3, and the other raw materials and preparation process remain the same as in Example 1.

[0054] Example 9

[0055] Compared with Example 1, in this example, vinyl polyborosilane is replaced by vinyl polyborosilane prepared in Preparation Example 4, and the remaining raw materials and preparation process remain the same as in Example 1.

[0056] Example 10

[0057] Compared with Example 1, the inorganic nanofiller (carbon nanotube) in this example is replaced with layered graphite oxide, and the other raw materials and preparation process remain the same as those in Example 1.

[0058] Comparative Example 1

[0059] Compared with Example 1, in this comparative example, vinyl polyborosilane is replaced with methyl vinyl silicone rubber, and the other raw materials and preparation process remain the same as those in Example 1.

[0060] Comparative Example 2

[0061] Compared with Example 1, the amount of vinyl polyborosilane in this comparative example is increased to 8 parts, and the other raw materials and preparation process remain the same as those in Example 1.

[0062] Comparative Example 3

[0063] Compared with Example 1, this comparative example does not add inorganic nanofiller (carbon nanotubes), and the remaining raw materials and preparation process remain the same as those of Example 1.

[0064] Comparative Example 4

[0065] Compared with Example 1, this comparative example does not add inorganic nanofiller (carbon nanotube) and vinyl polyborosilane, and the remaining raw materials and preparation process remain the same as those in Example 1.

[0066] Performance tests were performed on Examples 1 to 10 and Comparative Examples 1 to 3:

[0067] Combustion grade test: Limiting oxygen index determination, according to the national standard GB / T2406-2009 test, the sample size is 100mm×5mm×3mm; UL-94 test, according to the national standard GB / T10707-2008 test, the sample size is 130mm×13mm×3mm. The results are shown in Table 2:

[0068] Table 2

[0069] project LOI / %±0.2 UL-94 Example 1 29.2 V-0 Example 2 29.1 V-0 Example 3 29.6 V-0 Example 4 29.7 V-0 Example 5 29.3 V-0 Example 6 29.4 V-0 Example 7 29.1 V-0 Example 8 29.3 V-0 Example 9 29.0 V-0 Example 10 29.3 V-0 Comparative Example 1 28.9 V-0 Comparative Example 2 29.2 V-0 Comparative Example 3 28.5 V-0 Comparative Example 4 26.4 V-1

[0070] It can be seen from the test results that the high temperature resistant foamed silica gel material prepared by the present invention has good flame retardant properties.

[0071] The damping performance of the prepared high-temperature resistant foamed silicone material when used as a damping material was tested. The sample was cut into a dumbbell shape of 10×2×1mm, and the loading gap was adjusted to 1mm. Damping performance: The damping performance was tested using a solid rheology analyzer in the range of room temperature to minus 90°C, with a frequency of 10Hz and a heating rate of 3°C / min. Effective damping temperature range (the temperature range with tanδ≥0.25 is the effective temperature range) and maximum loss factor

[0072] Table 3

[0073] project Effective damping temperature range Maximum loss factor Example 1 65.54 0.68 Example 2 78.45 0.71 Example 3 70.07 0.68 Example 4 78.67 0.71 Example 5 65.87 0.68 Example 6 78.55 0.71 Example 7 62.66 0.67 Example 8 65.59 0.68 Example 9 60.13 0.67 Example 10 60.25 0.67 Comparative Example 1 52.56 0.66 Comparative Example 2 50.42 0.66 Comparative Example 3 30.69 0.57 Comparative Example 4 29.89 0.56

[0074] According to the test data recorded in Tables 2 and 3, the high-temperature resistant foamed silicone material prepared by the present invention has good damping performance and excellent flame retardancy. The damping performance of the foam material is related to the foam pore size and the pore density. The smaller the pore size and the larger the pore density, the better the damping performance. According to the results recorded in Examples 1 to 6, it can be seen that increasing the amount of inorganic nanofiller appropriately can enhance the viscosity between the polymer matrix of the high-temperature resistant foamed silicone material, which is beneficial to the formation of small-pore foam. Therefore, adding an appropriate amount of inorganic nanofiller is beneficial to increasing the pore density.

[0075] In Example 8-Example 9, the proportion of BO and phenyl groups in vinyl polyborosilane is adjusted. In the form of vinyl polyborosilane as raw material, BO is not only introduced into the structure of high temperature foaming silica gel material (having dynamic bond effect to limit segment motion, effectively reducing sensitivity to temperature, increasing segment motion internal friction, and improving damping performance), but also phenyl groups are introduced (π-π interaction, increasing intramolecular friction and improving loss factor), therefore, the proportion of phenylboric acid in vinyl polyborosilane is appropriately increased, for the damping and flame retardant properties of the material. Different inorganic nanofillers are added in Example 10, and there are also certain differences in improving the damping properties of the material. In summary, the addition of too much inorganic nanofiller and vinyl polyborosilane will cause the high temperature foaming silica gel material matrix to accumulate and form agglomerates, which will form nucleation points during the foaming process, and then form large-aperture pores, affecting the improvement of damping performance. It is necessary to make certain adjustments to the raw material ratio, broaden the damping temperature range to achieve the regulation of thermodynamic properties in a large range and improve flame retardant properties.

[0076] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high temperature resistant foamed silica gel material, characterized in that: The steps include: The first step is to add 95-97 parts of methyl vinyl silicone rubber and 3-5 parts of vinyl polyborosilane into an internal mixer for plasticization, then add 4 parts of hydroxy silicone oil and 40 parts of white carbon black for mixing, and cool to obtain a rubber mixture, and add 2-3 parts of inorganic nanofiller and 2 parts of vulcanizing agent to the rubber mixture and thinly pass at room temperature to obtain a composite material; The second step is to pre-vulcanize the composite material; then perform supercritical CO2 foaming, and finally perform post-vulcanization; The vinyl polyborosilane is prepared by the following steps: Under nitrogen protection, phenylboric acid and 1,2-dichloroethane were mixed, and an unsaturated silane coupling agent was added after heating to dissolve, and the mixture was stirred at 80°C for 8 hours, then cooled to 20°C, allowed to stand for 8 hours, concentrated under reduced pressure to remove the solvent, and dried under vacuum at 60°C to constant weight to obtain vinyl polyborosilane; The inorganic nanofiller is one of carbon nanotubes and layered graphite oxide; The unsaturated silane coupling agent is at least one of 3-trimethoxysilane propyl acrylate, γ-methacryloxypropyl trimethoxysilane, vinyl trimethoxysilane and allyl trimethoxysilane.

2. The method for preparing a high temperature resistant foamed silica gel material according to claim 1, characterized in that: In the first step, the plasticizing conditions are: temperature of 100-105°C and rotation speed of 55-60r / min.

3. The method for preparing a high temperature resistant foamed silica gel material according to claim 1, characterized in that: In the second step, the pre-curing conditions are: pre-curing at 125°C and 10MPa for 4-8min; The conditions for supercritical CO2 foaming are: foaming temperature 60°C, foaming pressure 6MPa; The post-vulcanization conditions are as follows: the foamed sample is vulcanized at 165°C and a pressure of 100 bar for 40 min, and then heat treated at 190°C for 3 h.

4. The method for preparing a high temperature resistant foamed silica gel material according to claim 1, characterized in that: The molar ratio of the phenylboric acid to the unsaturated silane coupling agent is 1.5-2:

1.

5. The method for preparing a high temperature resistant foamed silica gel material according to claim 1, characterized in that: The molar fraction of vinyl in the methyl vinyl silicone rubber is 0.13% to 0.20%; The specific surface area of ​​white carbon is 200±30m 2 / g; The inherent viscosity of hydroxyl is 100CS.

6. A high temperature resistant foamed silica gel material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Silicone rubber foaming material and preparation method thereof

    CN106189260A

  • High-damping shock-resistant organosilicone foam

    CN108912694A

  • Preparation method of high-damping shock-resistant organosilicone foam

    CN109161209A